Frequency-Following Response (FFR) in Military Pilots - Martins-Moreira, Graziela Maria; Durante, Alessandra Spada (International Archives of Otorhinolaryngology, 2020)
Introduction Good hearing in pilots, including central auditory skills, is critical for flight safety and the prevention of aircraft accidents. Pure tone audiometry alone may not be enough to assess hearing in the members of this population who, in addition to high noise levels, routinely face speech recognition tasks in non-ideal conditions.Objective To characterize the frequency-following response (FFR) of a group of military pilots compared with a control group.Methods Twenty military pilots in the Study Group and 20 non-pilot military personnel, not exposed to noise in their work, in the Control Group, all with normal hearing, aged between 30 and 40 years old, completed a questionnaire to assess their hearing habits, and their FFRs were measured with a /da/ syllable (duration 40 milliseconds, speed 10.9/s), at 80 dB NA in the right ear. All procedures were approved by the ethical committee of the institution. Statistical analysis was performed using the t-Student or Mann-Whitney tests for quantitative variables, and the Fisher or chi-squared tests for qualitative variables, and a value of p < 0.05 was considered to be statistically significant.Results There was no significant difference between the groups regarding auditory habits. In the FFR, wave amplitudes A (p = 0.01) and C (p = 0.04) were significantly lower in the Study Group.Conclusion Working as a military pilot can be a crucial factor in determining an individual's typical FFR pattern, demonstrated in the present study by statistically significant reductions in the amplitudes of the A and C waves.
Keywords: hearing; electrophysiology; cochlear nerve; brainstem auditory evoked potentials; speech perception